SPATIAL ANALYSIS OF KLASSEN TYPOLOGY OF BANJARBAKULA METROPOLITAN URBAN AREA: REGIONAL AND SECTORAL APPROACHES - Nor Aufa Azizah; Fitriyadi Fitriyadi; Ahmad Yunani (Adisam Publisher, 2025)
This study analyzes the inequality of economic development in the Banjarbakula Metropolitan Urban Area, emphasizing the spatial and sectoral distribution of growth. The objective of the study is to classify regencies and cities, as well as economic sectors, according to the Klassen Typology and to map core-periphery patterns as a basis for formulating more integrated and inclusive metropolitan development policies. The study uses a quantitative descriptive approach using secondary data from the 2020-2024 GRDP (Gross Domestic Product) and population for five regencies and cities in Banjarbakula, as well as the average for South Kalimantan Province. These data are analyzed through growth calculations and GRDP per capita, regional and sectoral Klassen Typology classifications, and then visualized in a Geographic Information System. The results indicate Banjarmasin City as a developed and fast-growing region, Banjarbaru City as an area with potential for rapid development, while Banjar, Barito Kuala, and Tanah Laut Regencies are relatively lagging behind. Sectorally, the central Banjarmasin-Banjarbaru corridor is dominated by advanced service and trade sectors, while the peripheral areas still rely on low-productivity primary sectors, requiring more targeted policy intervention.